Pelatihan Desain Grafis Perkantoran Bagi Pegawai Kecamatan di Kabupaten Sleman - Mochamad Hanafi; Sutirman Sutirman; Wahyu Rusdiyanto; Farres Radhwa Raihanah; Syifa Maulaya Rosyida; Afan Nasrul Wibisono; Avrelia Eka Rahayu; Niki Aulia Febianti; Maulidda Rohmawati; Cahyaning Mulat Ayu Eriyanti; Reny Oktavina Refwalu (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2025)
Office workers are currently required to be able to use technology and information, one of which is graphic design skills. This activity aims to provide graphic design training for sub-district employees in Sleman Regency. This training activity is expected to be able to overcome the problems of sub-district employees who need to improve graphic design skills in office tasks. The methods used in this community service activity include: 1) lectures, the lecture method is used to provide explanations to participants regarding the basic concepts of Corel Draw X7 and the urgency of graphic design in office work. 2) Question and answer, the question and answer method is used to identify issues related to the lecture material and to answer difficulties and problems that participants often face in terms of office graphic design. 3) Practice and assistance in graphic design training, the training is carried out using direct practice methods. Specifically, participants are given training in making business card designs using the Corel Draw X7 application. The community service activities have been carried out well and have provided knowledge and skills in the field of office graphic design for sub-district employees in Sleman Regency. The knowledge and skills delivered are theory and practice regarding office graphic design. The training was attended by 25 participants or 89.3% of the set target.